2007
DOI: 10.1128/jcm.00706-06
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between the AMPLICOR Human Papillomavirus Test and the Hybrid Capture 2 Assay in Detection of High-Risk Human Papillomavirus and Diagnosis of Biopsy-Confirmed High-Grade Cervical Disease

Abstract: Infection with human papillomavirus (HPV) has been detected in 95 to 100% of cervical cancers, the second most common female cancer worldwide (30), and persistent infection with high-risk HPV (HR-HPV) types is known to be the first step in the process of carcinogenesis. Several epidemiologic and molecular studies suggest the use of HPV testing in order to improve the efficacy of population-based screening programs for cervical cancer. HPV testing has been found to be useful for triaging minor cytological abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…High concordance between Hybrid Capture II and Amplicor has been shown previously (15,(19)(20)(21) However, our results suggest that both tests might benefit from adjusting their positivity cutoff values (to z2 RLU/PC for Hybrid Capture II and z1 for Amplicor), which would improve their specificity and PPV, while having …”
Section: (C) P16mentioning
confidence: 43%
“…High concordance between Hybrid Capture II and Amplicor has been shown previously (15,(19)(20)(21) However, our results suggest that both tests might benefit from adjusting their positivity cutoff values (to z2 RLU/PC for Hybrid Capture II and z1 for Amplicor), which would improve their specificity and PPV, while having …”
Section: (C) P16mentioning
confidence: 43%
“…5 [50,55]. In ten studies comparing the analytical and clinical performance of Amplicor with hc2 on different patient populations (mainly selected) and using different cut-off values, Amplicor showed 83.0-92.8% agreement with hc2, with k values ranging from 0.46-0.92 [37,49,51,[53][54][55][56][57][58][59]. All ten comparative studies clearly showed that Amplicor is analytically more specific than hc2 for detecting targeted hr-HPV types, mainly due to hc2 cross-reactivity with nontargeted lr-HPVs.…”
Section: Cervista Hpv Hr Testmentioning
confidence: 99%
“…Several studies, which included more that 15,000 patients in total, have compared the analytical and clinical performance of Amplicor with hc2 or with other commercial HPV tests or clinical criteria [37,[49][50][51][52][53][54][55][56][57][58][59][60][61]. Amplicor performed well in the prediction of CIN2+ lesions in women with abnormal cervical smears, using colposcopic biopsy and liquid-based cytology as the reference standards [60].…”
Section: Cervista Hpv Hr Testmentioning
confidence: 99%
“…Linear Array uses the PGMY09/11 L1 consensus primer system and includes coamplification of a human cellular target, h-globin, as an internal control. Detection and HPV genotyping are achieved using a reverse line-blot method and this test includes probes to genotype for 37 anogenital HPV types [6, 11, 16, (13,14). A positive cutoff point of 0.2 was used.…”
Section: Methodsmentioning
confidence: 99%